Implementasi Metode Yanbu’a dalam Pembelajaran Al-Qur’an di Pondok Pesantren Arriyadl Putri - Muhamad Alfi Halimi; Marita Lailia Rahman; Abbas Sofwan Matlail Fajar (Populer: Jurnal Penelitian Mahasiswa, 2025)
The expertise of teaching and learning a science must go through a learning process and is supported by the existence of proportional methods and techniques. Yanbu'a method is a method used to learn, read, write and memorize the Qur'an. The growing number of students at the Arriyadl Pesantren Putri demands changes in various aspects. Based on this, it is necessary to learn to read the Qur'an with a method. The method chosen is to use the Yanbu'a method located in the Arriyadl Putri Islamic Boarding School. The purpose of this study was to determine how the application of learning and evaluation of the yanbu'a method. The research method uses a qualitative method based on the philosophy of positivism which is used to examine naturalistic phenomena. Data collection techniques using participant observation, in-depth interviews and document studies. The data validity test uses triangulation techniques and data analysis uses mile and huberman interactive analysis, namely data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the study include a. The implementation of the Yanbu'a Method in learning the Qur'an at Madrasah Diniyyah Qur'aniyyah Arriyadl Putri Ringinagung is carried out with 2 learning systems, namely classical or group and individual learning, namely by reading and listening and sorogan techniques. The learning process includes opening, content and closing. The learning process is well scheduled and organized, the material for each volume, memorization and other readings in one week have been framed for learning effectiveness. b. The evaluation of learning the Yanbu'a method at MDQ Arriyadl Putri can be said to be successful, although not yet fully maximized. The implementation of the evaluation of learning to read the Qur'an at MDQ Yanbu'a consists of several stages, starting from daily tests commonly called page increment tests, volume increment tests, to the final test organized by the Muraqabah Yanbu'a Institute of Kediri district.